Liver sinusoidal endothelial cell expressed vascular cell adhesion molecule 1 promotes liver fibrosis - Guo, Qianqian; Furuta, Kunimaro; Islam, Shahidul; Caporarello, Nunzia; Kostallari, Enis; Dielis, Kobe; Tschumperlin, Daniel J.; Hirsova, Petra; Ibrahim, Samar H. (Frontiers in Immunology, 2022)
Background During liver injury, liver sinusoidal endothelial cells (LSECs) dysfunction and capillarization promote liver fibrosis. We have previously reported that the LSEC vascular cell adhesion molecule 1 (VCAM1) plays a key role in liver inflammation in nonalcoholic steatohepatitis (NASH) and we now aim to uncover its role in LSEC capillarization and liver fibrosis. Methods Wild-type C57BL/6J mice were fed either chow or high fat, fructose and cholesterol diet to induce NASH and treated with either anti-VCAM1 neutralizing antibody or control isotype antibody. Inducible endothelial cell-specific Vcam1 deleted mice (Vcam1Δend) and control mice (Vcam1fl/fl) were fed choline-deficient high-fat diet (CD-HFD) to induce NASH or injected with carbon tetrachloride to induce liver fibrosis. LSECs isolated from Vcam1fl/fl or Vcam1Δend and hepatic stellate cells (HSCs) isolated from wild-type mice were cocultured in a 3-D system or a μ-Slide 2 well co-culture system. Results Immunostaining for Lyve1 (marker of differentiated LSECs) was reduced in Vcam1fl/fl mice and restored in Vcam1Δend mice in both NASH and liver fibrosis models. Co-immunostaining showed increased α-smooth muscle actin in the livers of Vcam1fl/fl mice in areas lacking Lyve1. Furthermore, scanning electron microscopy showed reduced LSEC fenestrae in the Vcam1fl/fl mice but not Vcam1Δend mice in both injury models, suggesting that VCAM1 promotes LSEC capillarization during liver injury. HSCs profibrogenic markers were reduced when cocultured with LSECs from CD-HFD fed Vcam1Δend mice compared to Vcam1fl/fl mice. Furthermore, recombinant VCAM1 activated the Yes-associated protein 1 pathway and induced a fibrogenic phenotype in HSCs in vitro, supporting the profibrogenic role of LSEC VCAM1. Conclusion VCAM1 is not just a scaffold for leukocyte adhesion during liver injury, but also a modulator of LSEC capillarization and liver fibrosis.